1985
DOI: 10.1148/radiology.154.1.3880607
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular filtration rate determined in conjunction with routine renal scanning.

Abstract: A method has been developed to estimate glomerular filtration rate using computer evaluation of images obtained during routine renal scanning. The technique requires less than 40 minutes of imaging time, requires only a single blood sample, and correlates highly with 24 hour creatinine clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The “gold standard” for the determination of GFR has been considered to be that of continuous infusion of inulin with urine and plasma sampling; however this method is technically difficult and is rarely performed in a clinical setting. Renal DTPA clearance can be determined from: (a) Measurement of activity in single or multiple blood samples[ 6 7 8 ] (b) from the rate of removal of activity from blood or tissue[ 9 ] (c) from the rate of appearance of tracer in urine[ 10 ] and (d) from the rate of renal tracer uptake. [ 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The “gold standard” for the determination of GFR has been considered to be that of continuous infusion of inulin with urine and plasma sampling; however this method is technically difficult and is rarely performed in a clinical setting. Renal DTPA clearance can be determined from: (a) Measurement of activity in single or multiple blood samples[ 6 7 8 ] (b) from the rate of removal of activity from blood or tissue[ 9 ] (c) from the rate of appearance of tracer in urine[ 10 ] and (d) from the rate of renal tracer uptake. [ 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Further, plasma clearance of Tc-99m-DTPA correlates well with inulin clearance (standardized estimation error is 3.5 ml/min). [ 10 17 ] The alternative methods used, such as DPSM and SPSM were derived from empirical analysis of the relationship between the reference GFR and the volume of distribution and plasma concentration at sample time. [ 1 18 ] Some studies have also shown that the DPSM in a mono-compartment model was proved to be more accurate in GFR determination than the SPSM.…”
Section: Discussionmentioning
confidence: 99%
“…The serum creatinine level was measured at 1, 3, 6 and 12 months and at the most recent follow-up visit. The graft glomerular filtration rate (GFR) was measured by technetium-99m diethylene triamine peuta-acetic acid ('l'im'fc-DTPA) scans [5] and by the determination of the endogenous creatinine clearance. Moreover, the functional reserve of the graft was assessed by the simultaneous infusion of dopamine (2.5 Jlg/kg ·min) and a 10% solution of an amino acid preparation, Yamin N (80 mllh) for 12 h. During the procedure, a diuresis of at least 100 ml/h was maintained by orally administered fluids.…”
Section: Methodsmentioning
confidence: 99%
“…Many nuclear medicine solutions for estimating GFR using 99m Tcdiethylenetriaminepentaacetic (DTPA) are widely used today. Renal clearance can be estimated from the measurement of activity in single or multiple blood samples [2][3][4][5][6], from the rate of removal of activity from tissue or blood [7,8], from the rate of appearance of tracer in urine [9], and from the rate of renal tracer uptake. The most widely used gamma camera approach is a method introduced by Gates using approximately 3 mCi (111 MBq) of 99m Tc-DTPA and measuring the dosage in the syringe by counting it 20 cm from the face of a gamma camera before and following injection [10][11][12].…”
Section: Introductionmentioning
confidence: 99%